HUBUNGAN INDUSTRIAL: MENELISIK KONSTRUKSI EKONOMI ISLAM - Jalil, Abdul (EQUILIBRIUM, 2017)
The true development is an attempt to liberate himself from poverty and from a dwarf view of himself. Development is dedicated to fostering self-esteem and the ability to make choices about the future. Its industrial relations, in the sense of the relationship between the person doing the work on a person or a legal entity, has already begun with slavery by slaves and servants. The 'wages' they receive are food, clothing and housing. In its development, this concept has given rise to industrial mechanization that is still looking for form. The pattern of partnership between employers and workers has not gone well. Construction of Islamic Economics mengideaalkan industrial system with a partnership pattern that combines shirkah inan and ijarah that allows the existence of profit-loss sharing, so that no party is harmed, either workers or employers. Inan shirkah system in its development provides three alternatives, namely; Employee ownership, Production Sharing and Profit-sharing. With the choice of these patterns, the development of the industry will be in harmony with the humanity and economy, not just the pursuit of growth and rent which in turn will be trapped in capitalization and dehumanization